Liquid metal embrittlement of an Fe10Cr4Al ferritic alloy exposed to oxygen-depleted and -saturated lead-bismuth eutectic at 350°C. (1st April 2020) - Gong, Xing; Chen, Jiajun; Hu, Feiyu; Xiang, Congying; Yu, Zhiyang; Xiao, Jun; Wang, Hui; Gong, Haoran; Wang, Hao; Liu, Chaohong; Deng, Yangbin; Pang, Bo; et al.
Highlights: The LME susceptibility of Fe10Cr4Al was tested in LBE at 350 °C. This alloy is highly susceptible to LME. Surface oxides can delay LME. LME-induced fracture is dominated by cleavage and intergranular cracking. Abstract: Liquid metal embrittlement (LME) of an Fe10Cr4Al (wt%) ferritic alloy was tested in lead-bismuth eutectic (LBE) at 350 °C using slow strain rate tensile tests. The results show that this alloy is highly susceptible to LME. The strong LME effect is manifested by a substantial reduction in ductility and completely cleaved fracture surfaces. Transgranular cleavage and intergranular cracking are the major fracture modes. The LME susceptibility is slightly weaker in oxygen-saturated LBE than oxygen-depleted LBE due to the presence of a double-layer scale consisting of magnetite and Al-rich spinel. The oxide scale is fragmented, indicative of a brittle nature.